2023
DOI: 10.3390/ijms24021725
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Pan-Cancer Analysis Reveals Prognostic Role of the Erythroferrone (ERFE) Gene in Human Malignancies

Abstract: The erythroferrone gene (ERFE), also termed CTRP15, belongs to the C1q tumor necrosis factor-related protein (CTRP) family. Despite multiple reports about the involvement of CTRPs in cancer, the role of ERFE in cancer progression is largely unknown. We previously found that ERFE was upregulated in erythroid progenitors in myelodysplastic syndromes and strongly predicted overall survival. To understand the potential molecular interactions and identify cues for further functional investigation and the prognostic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 61 publications
1
0
0
Order By: Relevance
“…ERFE, also known as CTRP15, is a member of the C1q tumor necrosis factor-related protein family. In a pan-cancer study, Xu et al [42] found that ERFE overexpression indicated poor prognosis of breast cancer, colon cancer, pancreatic cancer, and renal clear cell carcinoma, consistent with the results of this study. This aspect requires further functional analysis and may have potential clinical value, as ERFE could be developed as a therapeutic target for CRC.…”
Section: Discussionsupporting
confidence: 91%
“…ERFE, also known as CTRP15, is a member of the C1q tumor necrosis factor-related protein family. In a pan-cancer study, Xu et al [42] found that ERFE overexpression indicated poor prognosis of breast cancer, colon cancer, pancreatic cancer, and renal clear cell carcinoma, consistent with the results of this study. This aspect requires further functional analysis and may have potential clinical value, as ERFE could be developed as a therapeutic target for CRC.…”
Section: Discussionsupporting
confidence: 91%